'I started to feel not ashamed of who I was': transracially adopted adults and adoption support. (December 2014) - Harris, Perlita
Transracially adopted adults are largely invisible as users of adoption support services in England and their voices are rarely heard in discussions about appropriate provision. This article reports findings from interviews with transracially adopted adults and transracially adopted adult participants at a lesbian, gay and bisexual focus group, carried out as part of a mixed-method study of service users' views and experiences of post-adoption services delivered by an independent agency. The article opens by outlining the policy context and what is known from existing research about the experiences of domestic transracially adopted adults. It then considers the experiences of 12 adults receiving support services. Drawing on their own words, it describes the difference that adoption support services can make, before highlighting gaps in existing provision and identifying the support needs specific to this group.